UNDERSTANDING THE IMPACT OF PCOS ON WOMEN'S QUALITY OF LIFE: A SCOPING REVIEW - Setyawati, Anita; Nuraeni, Rina; Solichah, Nur Umi Aminatus (Journal of Maternity Care and Reproductive Health, 2025)
Approximately 25% of women of reproductive age worldwide are affected with polycystic ovarian syndrome (PCOS).  A number of research have concentrated on evaluating the quality of life of women diagnosed with PCOS and related health issues.  This study was undertaken to assess the quality of life in women with PCOS.  This research constitutes a scoping review grounded in the Arksey and O'Malley paradigm.  A systematic literature search was performed in CINAHL Plus with Full-Text, PubMed, and Scopus utilising the search phrases "female OR woman OR women OR females" AND "PCOS OR polycystic ovary syndrome OR polycystic ovarian syndrome" AND "quality of life."  In accordance with the PRISMA-ScR methodology, 26 papers were selected for analysis in this study.  This scoping research revealed that the majority of women with PCOS encounter a diminished quality of life.  Demographic factors, anthropometric measurements, sex hormones, metabolic parameters, and sedentary behaviour contribute to this diminished quality of life.  Certain women practise lifestyle management, including emotional regulation and dietary control, to enhance their quality of life.  Medical professionals must evaluate the therapy and counselling modalities that can enhance the quality of life for women with PCOS.  Additional research is required to ascertain the correlation between the severity of PCOS symptoms and women's quality of life. Keywords: PCOS, quality of life, women.